Pola Pengasuhan terhadap Anak Dihubungkan dengan Hukum Perlindungan Anak di Kelurahan Pasanggrahan Kota Bandung - Krisnamurti, Hana (Jurnal Pengabdian Tri Bhakti, 2020)
Violation cases of children rights in every years more increase. Indonesian Child Protection Commision said that complaints to KPAI in 2015 were 4309 cases, after that in 2016 up to 4622. In 2017 were 4579 cases and in2018 reaching 4885 cases This phenomena its happened in society based on information from Indonesian Child Protection Commision that every year more and more increase. The fact that Violation cases of children rights caused og parents doesn’t know and realize about Child Protection Laws. Due to this problem, urgently needed socialize ang law counseling in giving a knowledge and understanding to the people, especially parental regarding a child’s rights guarantee in Child Protection Law then to provide assistance in preparing legal product, rules and assistance in preparing working program, its expected this activity will have awarnesess and attention to be able in helping government regarding a buse of child cases. The methode used is counseling and getting an outreach and assistance of each participants will be given a hardcopy materials/discussion/asking a question and answers and assistance to create a child friendly environment in order to realize a child protection and to prevent of a child against the law and to minimize increasing a numbers of abuse child cases.